(untitled) (Journal of Mathematical Study, 2021)
The matrix exponential formulae are very important tools in diverse fields of mathematical physics, in particular, they are also useful in studying quantum information theory. In this paper, we survey results related to matrix exponential thoroughly. The purpose of the article is pedagogical.